2006
DOI: 10.1126/science.1127981
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of an Infectious P22 Virion Shows the Signal for Headful DNA Packaging

Abstract: Bacteriophages, herpesviruses, and other large double-stranded DNA (dsDNA) viruses contain molecular machines that pump DNA into preassembled procapsids, generating internal capsid pressures exceeding, by 10-fold, that of bottled champagne. A 17 angstrom resolution asymmetric reconstruction of the infectious P22 virion reveals that tightly spooled DNA about the portal dodecamer forces a conformation that is significantly different from that observed in isolated portals assembled from ectopically expressed prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
380
3
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 289 publications
(413 citation statements)
references
References 19 publications
29
380
3
1
Order By: Relevance
“…At the same time, DNA near the center of the capsid is highly disordered even though the global organization is coaxially-spooled. This is consistent with the DNA structures observed by cryo-EM in ε15 and P22 Lander et al, 2006). Besides this, neither of the two packaging motifs considered so far (Figures 2a and 2b) exhibit geometrically idealized conformations such those of Arsuaga et al (Arsuaga et al, 2002).…”
Section: Isometric Capsids With a Core: Simulation Of ε15supporting
confidence: 78%
See 3 more Smart Citations
“…At the same time, DNA near the center of the capsid is highly disordered even though the global organization is coaxially-spooled. This is consistent with the DNA structures observed by cryo-EM in ε15 and P22 Lander et al, 2006). Besides this, neither of the two packaging motifs considered so far (Figures 2a and 2b) exhibit geometrically idealized conformations such those of Arsuaga et al (Arsuaga et al, 2002).…”
Section: Isometric Capsids With a Core: Simulation Of ε15supporting
confidence: 78%
“…2D studies on the icosahedral phage T7 with a large protein core revealed that DNA forms a set of rings around the protein core and supported the coaxial spooling model (Cerritelli et al, 1997). Similar conformations were revealed by higher-resolution 3D reconstructions on phages ε15 and P22 Lander et al, 2006), which are both isomorphous to T7 (Agirrezabala et al, 2005). 3D density reconstruction of prolate ϕ29 showed a set of concentric ellipsoidal shells of DNA density (Tao et al, 1998;Xiang et al, 2006) but failed to resolve individual DNA strands.…”
Section: Introductionmentioning
confidence: 68%
See 2 more Smart Citations
“…These studies combine data from thousands of particles to produce three-dimensional images of the capsid and genomic DNA, allowing the visualization of several layers of DNA loops within the capsid. [11][12][13] Models of Tightly-Packed Viral DNA…”
Section: Dna Virusesmentioning
confidence: 99%